2005
DOI: 10.1038/sj.onc.1208983
|View full text |Cite
|
Sign up to set email alerts
|

Both PPARγ and PPARδ influence sulindac sulfide-mediated p21WAF1/CIP1 upregulation in a human prostate epithelial cell line

Abstract: Nonsteroidal anti-inflammatory drugs (NSAIDs) including sulindac sulfide are known to exert cancer chemopreventative activity in a range of cell lines. This activity has been shown to involve the upregulation of the cyclindependent kinase inhibitor p21 WAF1/CIP1 . It is also known that NSAIDs can act as peroxisome proliferator-activated receptor (PPAR) agonists and antagonists. In this study, we show that sulindac sulfide acts both as a PPARc agonist and a PPARd antagonist in an immortalized prostatic epitheli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 18 publications
(17 reference statements)
1
26
0
Order By: Relevance
“…It has recently been reported that up-regulation of p21, with associated growth suppression, following sulindac treatment may be mediated in part through activation of the nuclear receptor protein PPARγ (30). As shown in Figure 5A, PPARγ expression was maintained in polyp tissue in the absence of sulindac treatment.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has recently been reported that up-regulation of p21, with associated growth suppression, following sulindac treatment may be mediated in part through activation of the nuclear receptor protein PPARγ (30). As shown in Figure 5A, PPARγ expression was maintained in polyp tissue in the absence of sulindac treatment.…”
Section: Resultsmentioning
confidence: 99%
“…For example, sulindac can bind to and activate peroxisome proliferator-activated receptors (PPARs γ or δ), which have been shown to act as either a tumor suppressor or oncogene in colon cancer, respectively (28, 29). Also, in prostate cells, it has been shown that PPARγ is required for both growth inhibition and p21 up-regulation by sulindac sulfide (30). …”
Section: Introductionmentioning
confidence: 99%
“…For example, pioglitazone, a PPARg agonist inhibited p21-mediated prostate cancer cell growth (Hirsch et al, 2011). PPARg stimulates sulindac sulfide-mediated p21 expression in prostate epithelial cells (Jarvis et al, 2005). Soy peptide increased p21 in human breast MCF-7 tumour cells via inactivation of NF-kB, and thus inhibited their growth (Park et al, 2009).…”
Section: Figurementioning
confidence: 99%
“…NF-kB and PPARg are also important in p21-mediated cell cycle arrest of human cancer cells (Hellin et al, 2000;Prakobwong et al, 2011); the expression of p21 is increased in the resistant human cancer cells in a NF-kB-and PPARg-dependent manner (Chang and Miyamoto, 2006;Jarvis et al, 2005). Moreover, many investigators, using components and crude extracts isolated from the Magnolia family, have shown that p21-mediated cell cycle arrest leads to cell growth inhibition (Hahm and Singh, 2007;Lee et al, 2007;.…”
Section: Introductionmentioning
confidence: 99%
“…Regardless, the potential for 'receptor crossover' suggests that the ratio of PPARγ to PPARδ expression could alter both tumor biology and drug pharmacology. This is particular alarming given that the two receptors are co-expressed in most breast cancers and PPARδ has been implicated in promoting development and expansion of tumors from several tissue origins [24][25][26][27]. Clearly, an understanding of the role of each receptor in regulating growth of cancer cells should allow for future development of safer, yet effective PPAR modulators with potential therapeutic use for cancer.…”
Section: Introductionmentioning
confidence: 99%